Cost-effectiveness analysis of toripalimab plus chemotherapy versus standard chemotherapy in first-line treatment for extensive-stage small cell lung cancer: perspectives from the United States and China - Ouyang, Ming; Wang, Jiangbo; Zhang, Gaofeng; Huang, Bei; Deng, Lin; Deng, Lian; Lang, Wenwang (Frontiers in Pharmacology, 2025)
BackgroundToripalimab combined with chemotherapy has demonstrated significant clinical advantages in improving overall survival compared with chemotherapy alone as a first-line treatment for extensive-stage small-cell lung cancer (ES-SCLC).MethodAn economic evaluation was conducted using a Markov state-transition model to reflect the perspectives of the United States payer and Chinese healthcare systems. Primary outcomes included quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefit (INHB), and incremental net monetary benefit (INMB).ResultsBase-case analysis indicated that incorporating toripalimab into chemotherapy produced an ICER of $45,629.27 per QALY, exceeding China’s willingness-to-pay (WTP) threshold of $38,042.49 per QALY. Subgroup analyses revealed ICERs of $22,345.99 and $30,867.38 per QALY for patients with low intratumor heterogeneity (ITH-L) and A11+/B62- histology, respectively, both below the China WTP threshold. In contrast, in the United States, the additional cost led to unfavorable ICERs of $842,855.23, $328,694.61, and $520,412.03 per QALY for the overall population, the ITH-L subgroup, and the A11+/B62− subgroup, respectively, each exceeding the United States WTP threshold of $150,000.00.ConclusionThe combination of toripalimab and chemotherapy was not found to be a cost-effective first-line treatment for ES-SCLC in China or the United States, except for patients in China with ITH-L and A11+/B62- histology.